Kontribusi Baitul Maal Wa Tamwil (Bmt) Terhadap Ekonomi Nasabah Kreditur Di Bmt Sidogiri Kecamatan Sangkapura Bawean Kabupaten Gresik - Yusmita, Yusmita; Eni, Ulfa (JURISY: Jurnal Ilmiah Syariah, 2023)
ABSTRACT This paper raises and explains whether one of the non-bank financial institutions, namely Baitul Maal Wa Tamwil (BMT) Sidogiri Sangkapura Bawean Branch, has contributed to improving the economy of creditor customers or not. And if there is indeed a contribution, the researchers will re-measure how much the Baitul Maal Wa Tamwil (BMT) Sidogiri Sangkapura Bawean Branch contributes to improving the economy of creditor customers.In this study, the researcher chose Baitul Maal Wa Tamwil (BMT) Sidogiri Sangkapura Bawean Branch because BMT is a non-bank and sharia-based financial institution located on the island of Bawean. In addition, BMT Sidogiri Sangkapura also makes it easier for researchers to obtain the data needed for the purposes of this research.The research method that the researchers used in this study was a survey method with the Chi Square analysis technique. Survey research is research that takes samples from the population and uses a questionnaire as a primary data collection tool.In this study the technique was used to find out about the contribution of Baitul Maal Wa Tamwil (BMT) to the economy of creditor customers at BMT Sidogiri Sangkapura. Keywords: Contribution, Economy, Creditors